Impact‐induced muscle damage and urinary pterins in professional rugby: 7, 8‐dihydroneopterin oxidation by myoglobin. Issue 3 (13th March 2015) - Lindsay, A.; Healy, J.; Mills, W.; Lewis, J.; Gill, N.; Draper, N.; Gieseg, S. P.
Abstract : Muscle damage caused through impacts in rugby union is known to increase oxidative stress and inflammation. Pterins have been used clinically as markers of oxidative stress, inflammation, and neurotransmitter synthesis. This study investigates the release of myoglobin from muscle tissue due to force‐related impacts and how it is related to the subsequent oxidation of 7, 8‐dihydroneopterin to specific pterins. Effects of iron and myoglobin on 7, 8‐dihydroneopterin oxidation were examined in vitro via strong cation‐exchange high‐performance liquid chromatography (SCX‐HPLC) analysis of neopterin, xanthopterin, and 7, 8‐dihydroxanthopterin. Urine samples were collected from 25 professional rugby players pre and post four games and analyzed for myoglobin by enzyme‐linked immunosorbent assay, and 7, 8‐dihydroneopterin oxidation products by HPLC. Iron and myoglobin oxidized 7, 8‐dihydroneopterin to neopterin, xanthopterin, and 7, 8‐dihydroxanthopterin at concentrations at or above 10 μM and 50 μg/mL, respectively. All four games showed significant increases in myoglobin, neopterin, total neopterin, biopterin, and total biopterin, which correlated between each variable ( P  < 0.05). Myoglobin and iron facilitate 7, 8‐dihydroneopterin oxidation to neopterin and xanthopterin. In vivo delocalization of myoglobin due to muscle damage may contribute to oxidative stress and inflammation after rugby. Increased concentrations of biopterin and total biopterin may indicate production of nitric oxide and monoamine neurotransmitters in response to the physical stress.